Al borde de las cosas: sobre los límites de la identidad - Pacheco Pajuelo, Sergio Jesús (2024)
The present text develops a brief summary of some of the contents of my artistic project On the edge of things, an art installation presented inside the house of my maternal grandfather in Arequipa, Perú. In this study I address contemporary old age in its most degenerative state, confronted with the deterioration of the vital functions which are traditionally believed that identity is built on. The general decline in old age, as a research topic, raises the question of the possible loss or interruption of identity, an issue that I propose to understand as a liminal state of interruption. The final objective of this work is to present a critique of the concept of identity, through old age, as a category that validates existence, presenting important questions about the individual and their relationship with the processes of decline. In this writing I will not dwell on the discourses or in the detailed description of the artistic pieces, but –especially– in the motivations and the processes of creation and investigation of the same.